Matematică
ipavel1970
13

1) 5x - ( 5 - x ) = 2) -3x + ( - 3 + 4x ) = 3) ( 2x + 1 ) - ( x - 1 ) = 4) - ( 3x - 1 ) - ( 3x - 1 ) = 5) 2x + ( 3x - 2 ) - ( 5x - 3 ) = 6) - 2 - ( 2x - 5 ) - ( 1 - 4x ) = 7) ( 6x - 2) - 2x - ( 3x - 3 ) = 8) - x - ( 2x - 1 ) - ( - 4x + 3 ) = 9) 2x - ( -2 - x ) - ( x + 1 ) = ajutatima va rog imi trebuie pe maine:(

+1
(2) Răspunsuri
Lori111

rezolvarea e in poza. sper sa intelegi

vatamanuionela

1) 5x - ( 5 - x ) <=>5x-5+x<=>6x-5<=>x=5 pe 6 2) -3x + ( - 3 + 4x ) <=>-3x-3+4x<=>x=3 3) ( 2x + 1 ) - ( x - 1 ) <=>2x+1-x+1<=>x=2 4) - ( 3x - 1 ) - ( 3x - 1 ) <=>-3x+1-3x+1<=>-6x+2<=>x=2 pe 6 5) 2x + ( 3x - 2 ) - ( 5x - 3 ) <=>2x+3x-2-5x+3<=>0=1  Solutia e multimea vida 6) - 2 - ( 2x - 5 ) - ( 1 - 4x )< => -2-2x+5-1+4x<=>2x=2<=>x=1 7) ( 6x - 2) - 2x - ( 3x - 3 ) <=>6x-2-2x-3x+3<=>x=1 8) - x - ( 2x - 1 ) - ( - 4x + 3 )< =>-x-2x+1+4x-3<=>x-2 9) 2x - ( -2 - x ) - ( x + 1 )< = > 2x+2+x-x-1<=>2x=1<=>x=1 pe 2

Adaugă răspuns